Peran Lesson Study dalam Meningkatkan Kinerja Dosen dalam Perkuliahan di Jurusan Pendidikan MIPA FKIP UM METRO - Nyoto Suseno (Department of Physics Education, Universitas Mataram, 2015)
The goal of this study to explore the role of lesson study activity to improve lecturers performance at Department of math & science education, FKIP UM Metro. This is a descriptive research, using documentation and questionnaire method. The sources of data are Student, lecturer and supervisor. The analysis of data using quantitative and qualitative by doing triangulation based on self evaluation, student questionnaire and judgement team. The result found that (1) In General, The average of science lecturers performance are batter then before joined lesson study program, (2) Lecterers model have better performance than other how have natÃÂ joined, (3) Specialy for the lecturers how involved in lesson study have improving performance; (4) Learning result of the student are batter than before using lesson study. The recomendation of this reseach, the lesson study program used to be continued to support improving lecturers performance in learning.